Resin composition and molded article thereof

The resin composition, comprising a polycarbonate resin with a spiro ring structure and specific copolymers and epoxy resin, addresses the challenges of achieving balanced properties in transparency, hardness, impact resistance, and light resistance, while preventing yellowing, resulting in a highly effective industrial solution.

JP7658759B2Active Publication Date: 2025-04-08TEIJIN LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021037502
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-04-08
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Existing resin compositions for transparent materials face challenges in achieving a balance between transparency, surface hardness, impact resistance, moisture and heat resistance, and light resistance, while also preventing yellowing during molding.

Method used

A resin composition is developed that includes a polycarbonate resin with a specific spiro ring structure, a methyl methacrylate-methyl acrylate copolymer, a methyl methacrylate-alkyl acrylate-styrene copolymer, and an epoxy resin, optimized in weight ratios and molecular weights to enhance the desired properties.

Benefits of technology

The composition achieves excellent transparency, surface hardness, impact resistance, moisture-heat resistance, and light resistance, while suppressing yellowing due to heat history during molding, thereby providing a superior industrial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658759000001
    Figure 0007658759000001
  • Figure 0007658759000002
    Figure 0007658759000002
  • Figure 0007658759000003
    Figure 0007658759000003
Patent Text Reader

Abstract

To provide a resin composition which suppresses yellow discoloration due to a thermal history in molding, and has characteristics excellent in transparency, surface hardness, impact resistance, moist heat resistance and light resistance.SOLUTION: A resin composition contains 10-30 pts.wt. of a methyl methacrylate-alkyl acrylate-styrene copolymer (C), and 1-30 pts.wt. of an epoxy resin (D) based on 100 pts.wt. of the sum of a polycarbonate resin (A) containing 5-85 mol% of units (a) whose repeating unit is represented by a following formula (1), and a methyl methacrylate-methyl acrylate copolymer (B), and has a refraction index of the methyl methacrylate-alkyl acrylate-styrene copolymer (C) of 1.485 or more and 1.495 or less. (W is a 1-20C alkylene group, or a 6-20C cycloalkylene group, R is a 1-20C branched or linear alkyl group, or a 6-20C cycloalkylene group which may have a substituent group, and m is an integral number of 0-10.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing a specific polycarbonate resin, a methyl methacrylate-methyl acrylate copolymer, a methyl methacrylate-alkyl acrylate-styrene copolymer and an epoxy resin, and a molded article thereof. [Background technology]

[0002] Conventionally, methacrylic resins, polycarbonate resins (hereinafter sometimes referred to as PC), etc. are known as transparent resins, and they are used in a wide range of fields such as electrical and electronic components, optical components, automotive components, and mechanical components in the form of molded products, films, sheets, etc.

[0003] Methacrylic acid resins such as polymethyl methacrylate (hereinafter sometimes referred to as PMMA) have high transparency and high surface hardness (pencil hardness H to 3H), and are widely used as optical materials such as lenses and optical fibers. However, their glass transition temperature is low at about 100°C, and their heat resistance is poor, limiting their use in fields requiring heat resistance. Another problem is that they have low impact resistance.

[0004] Polycarbonate resins made from bisphenol A are widely used in vehicle applications and building materials because of their excellent heat resistance, impact resistance, flame retardancy, and transparency. Among these applications, high weather resistance is required, especially for those used outdoors, but the weather resistance of polycarbonate resins is generally not as good as other transparent materials such as acrylic resins, and yellowing and devitrification occur when exposed to the outdoors. In addition, there is a problem that the surface is very soft (pencil hardness 4B to 2B) and easily scratched.

[0005] It is known that blends of PC and PMMA are essentially incompatible and produce opaque materials. For example, Patent Document 1 shows that blends of PC and PMMA are opaque and do not exhibit the physical properties of both polymers.

[0006] A resin composition using a polycarbonate resin having a special structure and an acrylic resin has been reported (Patent Document 2), and excellent transparency, weather resistance and surface hardness have been achieved. However, according to the study by the present inventors, it has been found that the resin composition described in Patent Document 2 has a problem with impact resistance and has low Charpy impact strength. Furthermore, it has been found that the resin composition described in Patent Document 2 has significant deterioration in moist heat resistance and light resistance. Therefore, in a resin composition of a polycarbonate resin and an acrylic resin, a resin composition that suppresses yellowing during molding and has good transparency, surface hardness, impact resistance, moist heat resistance and light resistance has not been reported so far. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] U.S. Pat. No. 4,319,003 [Patent Document 2] JP 2015-232091 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a resin composition which is inhibited from yellowing due to thermal history during molding and has excellent properties such as transparency, surface hardness, impact resistance, moist heat resistance and light resistance. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted extensive research and have discovered that by incorporating a methyl methacrylate-methyl acrylate copolymer, a methyl methacrylate-alkyl acrylate-styrene copolymer, and an epoxy resin into a polycarbonate resin containing a specific spiro ring structure, a resin composition can be obtained that has excellent properties such as inhibition of yellowing due to thermal history during molding, transparency, surface hardness, impact resistance, moist heat resistance, and light resistance, and have thus completed the present invention.

[0010] That is, according to the present invention, the object of the invention is achieved as follows.

[0011] 1. A resin composition comprising 100 parts by weight of a total of a polycarbonate resin (A) containing 5 to 85 mol % of repeating units of unit (a) represented by the following formula (1) and a methyl methacrylate-methyl acrylate copolymer (B), 10 to 30 parts by weight of a methyl methacrylate-alkyl acrylate-styrene copolymer (C) and 1 to 30 parts by weight of an epoxy resin (D), wherein the refractive index of the methyl methacrylate-alkyl acrylate-styrene copolymer (C) is 1.485 or more and 1.495 or less.

[0012] [ka]

[0013] (In the formula, W represents an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms, R represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent, and m represents an integer of 0 to 10.)

[0014] 2. A resin composition according to item 1 above, wherein the polycarbonate resin (A) comprises a carbonate unit (a) whose repeating unit is represented by the formula (1) and another carbonate unit (b), and the carbonate unit (b) is a carbonate unit (b) derived from at least one compound selected from the group consisting of an aliphatic diol compound, an alicyclic diol compound, and an aromatic dihydroxy compound.

[0015] 3. The resin composition according to item 1 or 2 above, wherein the weight ratio of the polycarbonate resin (A) to the methyl methacrylate-methyl acrylate copolymer (B) is 50:50 to 99:1.

[0016] 4. The resin composition according to any one of items 1 to 3 above, wherein the methyl methacrylate-methyl acrylate copolymer (B) contains 40 to 100 mol % of repeating units derived from methyl methacrylate.

[0017] 5. The resin composition according to any one of items 1 to 4 above, wherein the epoxy resin (D) has a molecular weight of 3,000 to 20,000.

[0018] 6. The resin composition according to any one of items 1 to 5 above, wherein a haze of a test piece having a thickness of 6.2 mm is 10% or less.

[0019] 7. A molded article obtained by molding the resin composition according to any one of items 1 to 6 above.

[0020] 8. A film or sheet formed from the resin composition according to any one of items 1 to 6 above. Effect of the Invention

[0021] The present invention provides a resin composition having excellent properties such as transparency, surface hardness, impact resistance, moist heat resistance and light resistance by adding a methyl methacrylate-alkyl acrylate-styrene copolymer (C) and an epoxy resin (D) to a composition of a polycarbonate resin containing a specific spiro ring structure and a methyl methacrylate-methyl acrylate copolymer, and therefore the industrial effects achieved are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will be described in detail below.

[0023] (Polycarbonate resin) The polycarbonate resin used in the resin composition of the present invention is a polycarbonate resin (A) containing 5 to 85 mol % of carbonate units (a) represented by the following formula (1) in all repeating units.

[0024] [ka]

[0025] (In the formula, W represents an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms, R represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent, and m represents an integer of 0 to 10.)

[0026] The unit (a) represented by the above formula (1) is derived from a diol having a spiro ring structure. Examples of the diol compound having such a spiro ring structure include alicyclic diol compounds such as 3,9-bis(2-hydroxyethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, 3,9-bis(2-hydroxy-1,1-diethylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, and 3,9-bis(2-hydroxy-1,1-dipropylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane.

[0027] Preferably, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane is used.

[0028] The polycarbonate resin used in the resin composition of the present invention contains the repeating unit (a) represented by the above formula (1) in 5 to 85 mol %, preferably 10 to 80 mol %, more preferably 15 to 75 mol %, and even more preferably 20 to 70 mol % of the total repeating units. When the unit (a) is within the above range, the resin composition does not become cloudy due to phase separation during extrusion or molding of the resin composition with the acrylic resin, and polymerization of the polycarbonate resin is easy without crystallization during polymerization, which is preferable.

[0029] The polycarbonate resin used in the resin composition of the present invention contains the unit (a) represented by the above formula (1), and is used as a copolymer with other carbonate units (b).

[0030] The carbonate unit (b) is preferably a carbonate unit (b) derived from at least one compound selected from the group consisting of an aliphatic diol compound, an alicyclic diol compound, and an aromatic dihydroxy compound. From the standpoint of surface hardness and weather resistance, the carbonate unit (b) is preferably a carbonate unit (b) derived from at least one compound selected from the group consisting of an aliphatic diol compound and an alicyclic diol compound.

[0031] Aliphatic diol compounds include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-n-butyl-2-ethyl-1,3-propanediol, and 2,2-diethyl-1,3-propanediol. Examples of the diol include 2,4-diethyl-1,5-pentanediol, 1,2-hexane glycol, 1,2-octyl glycol, 2-ethyl-1,3-hexanediol, 2,3-diisobutyl-1,3-propanediol, 2,2-diisoamyl-1,3-propanediol, and 2-methyl-2-propyl-1,3-propanediol. Of these, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol are preferably used.

[0032] Examples of the alicyclic diol compound include cyclohexanediols such as 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, and 2-methyl-1,4-cyclohexanediol; cyclohexanedimethanols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol; norbornane dimethanols such as 2,3-norbornane dimethanol and 2,5-norbornane dimethanol; tricyclodecane dimethanol, pentacyclopentadecane dimethanol, 1,3-adamantanediol, 2,2-adamantanediol, decalin dimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and isosorbide; and preferably used are cyclohexanedimethanol and isosorbide.

[0033] Examples of aromatic dihydroxy compounds include α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (bisphenol M), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, bisphenol A, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane (bisphenol AF), and 1,1-bis(4-hydroxyphenyl)decane, with bisphenol A being preferred.

[0034] The carbonate unit (b) is preferably contained in an amount of 15 to 95 mol %, more preferably 20 to 90 mol %, further preferably 25 to 85 mol %, and particularly preferably 30 to 80 mol % of all repeating units. When the unit (b) is within the above range, a resin composition having a better balance of transparency, surface hardness, and impact resistance can be obtained.

[0035] (Production method of polycarbonate resin) The polycarbonate resin is produced by a reaction means known per se for producing a normal polycarbonate resin, for example, a method of reacting a diol component with a carbonate precursor such as a carbonic acid diester. Next, the basic means for these production methods will be briefly described.

[0036] The transesterification reaction using a carbonic acid diester as a carbonate precursor is carried out by a method in which a predetermined ratio of diol components is heated and stirred with a carbonic acid diester under an inert gas atmosphere, and the alcohol or phenols produced are distilled off. The reaction temperature varies depending on the boiling point of the alcohol or phenols produced, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning of the reaction to distill off the alcohol or phenols produced. In addition, a terminal terminator, an antioxidant, etc. may be added as necessary.

[0037] The carbonic acid diester used in the transesterification reaction includes esters of aryl groups and aralkyl groups having 6 to 12 carbon atoms, which may be substituted. Specific examples include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, and m-cresyl carbonate. Among these, diphenyl carbonate is particularly preferred. The amount of diphenyl carbonate used is preferably 0.97 to 1.10 mol, more preferably 1.00 to 1.06 mol, per mol of the total of the dihydroxy compounds.

[0038] In the melt polymerization method, a polymerization catalyst can be used to increase the polymerization rate. Examples of such a polymerization catalyst include alkali metal compounds, alkaline earth metal compounds, nitrogen-containing compounds, and metal compounds.

[0039] As such compounds, organic acid salts, inorganic salts, oxides, hydroxides, hydrides, alkoxides, quaternary ammonium hydroxides, etc. of alkali metals or alkaline earth metals are preferably used, and these compounds can be used alone or in combination.

[0040] Examples of alkali metal compounds include sodium hydroxide, potassium hydroxide, cesium hydroxide, lithium hydroxide, sodium hydrogen carbonate, sodium carbonate, potassium carbonate, cesium carbonate, lithium carbonate, sodium acetate, potassium acetate, cesium acetate, lithium acetate, sodium stearate, potassium stearate, cesium stearate, lithium stearate, sodium borohydride, sodium benzoate, potassium benzoate, cesium benzoate, lithium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, disodium phenylphosphate, disodium salt, dipotassium salt, dicesium salt, and dilithium salt of bisphenol A, and sodium, potassium, cesium, and lithium salts of phenol.

[0041] Examples of alkaline earth metal compounds include magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, magnesium diacetate, calcium diacetate, strontium diacetate, barium diacetate, and barium stearate.

[0042] Examples of the nitrogen-containing compound include quaternary ammonium hydroxides having an alkyl or aryl group, such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and trimethylbenzylammonium hydroxide. Other examples include tertiary amines, such as triethylamine, dimethylbenzylamine, and triphenylamine, and imidazoles, such as 2-methylimidazole, 2-phenylimidazole, and benzimidazole. Other examples include bases or basic salts, such as ammonia, tetramethylammonium borohydride, tetrabutylammonium borohydride, tetrabutylammonium tetraphenylborate, and tetraphenylammonium tetraphenylborate.

[0043] Examples of the metal compound include a zinc aluminum compound, a germanium compound, an organotin compound, an antimony compound, a manganese compound, a titanium compound, and a zirconium compound. These compounds may be used alone or in combination of two or more.

[0044] The amount of the polymerization catalyst used is preferably 1×10 -9 ~1×10 -2 equivalent, preferably 1 x 10 -8 ~1×10 -5 equivalent, more preferably 1×10 -7 ~1×10 -3 is selected within the equivalent range.

[0045] A catalyst deactivator can also be added in the later stage of the reaction. Known catalyst deactivators can be effectively used as the catalyst deactivator, and among these, ammonium salts and phosphonium salts of sulfonic acid are preferred. Furthermore, salts of dodecylbenzenesulfonic acid such as tetrabutylphosphonium dodecylbenzenesulfonate and salts of paratoluenesulfonic acid such as tetrabutylammonium paratoluenesulfonate are preferred.

[0046] As the ester of sulfonic acid, methyl benzenesulfonate, ethyl benzenesulfonate, butyl benzenesulfonate, octyl benzenesulfonate, phenyl benzenesulfonate, methyl paratoluenesulfonate, ethyl paratoluenesulfonate, butyl paratoluenesulfonate, octyl paratoluenesulfonate, phenyl paratoluenesulfonate, etc. are preferably used. Among them, tetrabutylphosphonium dodecylbenzenesulfonate is most preferably used.

[0047] When at least one polymerization catalyst selected from alkali metal compounds and / or alkaline earth metal compounds is used, the amount of these catalyst deactivators used is preferably 0.5 to 50 mol, more preferably 0.5 to 10 mol, and even more preferably 0.8 to 5 mol, per mol of the catalyst.

[0048] (Specific viscosity:η SP ) The specific viscosity (η SP ) is preferably 0.2 to 1.5. When the specific viscosity is in the range of 0.2 to 1.5, the strength and molding processability of the molded article become better. It is more preferably 0.25 to 1.0, further preferably 0.3 to 0.7, and particularly preferably 0.3 to 0.5.

[0049] The specific viscosity referred to in the present invention is determined by using an Ostwald viscometer to measure a solution in which 0.7 g of polycarbonate resin is dissolved in 100 ml of methylene chloride at 20°C. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls]

[0050] The specific viscosity can be measured, for example, as follows. First, polycarbonate resin is dissolved in methylene chloride of 20 to 30 times its weight, and the soluble portion is collected by celite filtration. The solution is then removed and the mixture is thoroughly dried to obtain a solid soluble in methylene chloride. 0.7 g of the solid is dissolved in 100 ml of methylene chloride, and the specific viscosity at 20°C is determined using an Ostwald viscometer.

[0051] (Methyl methacrylate-methyl acrylate copolymer) As the acrylic resin used in the resin composition of the present invention, a methyl methacrylate-methyl acrylate copolymer (B), which is an acrylic resin as a thermoplastic resin, is used.

[0052] Also, monomers other than methyl methacrylate and methyl acrylate can be used, and examples of monomers used in copolymerization include the following compounds: for example, methacrylic acid, acrylic acid, benzyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, ethylhexyl ... Allyl (meth)acrylate, glycidyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, acrylic (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyl maleate Examples of the acrylic monomer include cyclooxyethyl, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, pentamethylpiperidyl (meth)acrylate, tetramethylpiperidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, cyclopentyl methacrylate, cyclopentyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, cycloheptyl methacrylate, cycloheptyl acrylate, cyclooctyl methacrylate, cyclooctyl acrylate, cyclododecyl methacrylate, and cyclododecyl acrylate. In addition, other monomers that can be polymerized with these acrylic monomers, such as polyolefin monomers and vinyl monomers (excluding styrene), may be used in combination. Two or more of these may be polymerized and used.

[0053] The methyl methacrylate-methyl acrylate copolymer (B) preferably contains 40 to 100 mol %, more preferably 50 to 100 mol %, and even more preferably 60 to 99 mol % of methyl methacrylate as a monomer component. When the proportion of methyl methacrylate as a monomer component is within the above range, the copolymer has excellent thermal decomposition resistance, is less likely to cause molding defects such as silver during molding, and has a good heat distortion temperature.

[0054] The molecular weight of the methyl methacrylate-methyl acrylate copolymer is not particularly limited, but as long as the weight average molecular weight is in the range of 30,000 or more and 300,000 or less, a composition having excellent mechanical properties and heat resistance can be provided without causing appearance defects such as flow unevenness when molded into a composition.

[0055] The acrylic resin used in the resin composition of the present invention preferably has a specific viscosity in the range of 0.12 to 0.55. If the specific viscosity is less than 0.12, the molded product may become brittle. If the specific viscosity is higher than 0.55, the melt viscosity of the resin may increase, resulting in poor moldability.

[0056] (Methyl methacrylate-alkyl acrylate-styrene copolymer) The resin composition of the present invention contains a methyl methacrylate-alkyl acrylate-styrene copolymer (C) as an impact modifier. The methyl methacrylate-alkyl acrylate-styrene copolymer is preferably a core-shell type consisting of a core which is a rubber-like polymer and a shell obtained by graft polymerization to the rubber-like polymer. By using a core-shell type impact modifier of a methyl methacrylate-alkyl acrylate-styrene copolymer, the dispersibility in polycarbonate is improved, and high impact strength and good light resistance tend to be obtained.

[0057] The average particle size of the impact modifier is preferably 5 to 500 nm. More preferably, it is 7 to 300 nm, further preferably 9 to 200 nm, and most preferably 10 to 180 nm. When the average particle size is 5 nm or more, more sufficient impact strength can be obtained. Furthermore, when the average particle size is 500 nm or less, the transparency of the resulting resin composition is more excellent. The average particle size is measured in the latex state of the rubber-like polymer and the graft copolymer. The volume average particle size can be measured using a measuring device, MICROTRAC UPA150 manufactured by Nikkiso Co., Ltd.

[0058] The rubber-like polymer corresponding to the core of the impact modifier preferably contains a methyl methacrylate-alkyl acrylate copolymer, which allows the resin composition of the present invention to have both transparency and impact strength, and is also preferable from the viewpoint of raw material costs.

[0059] Specific examples of the alkyl acrylate include ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate.

[0060] Furthermore, monomers other than methyl methacrylate and alkyl acrylate can also be used, and examples of monomers used in copolymerization include acrylic acid, methacrylic acid, ethyl methacrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and glycidyl methacrylate.

[0061] The glass transition temperature (Tg) of the rubber-like polymer is preferably 0° C. or lower from the viewpoint of improving impact resistance, more preferably −20° C. or lower, and further preferably −40° C. or lower.

[0062] The shell portion of the methyl methacrylate-alkyl acrylate-styrene copolymer (C) preferably contains a styrene polymer. Monomers other than styrene can also be used, and aromatic vinyl compounds such as α-methylstyrene, cyanide vinyl compounds such as acrylonitrile and methacrylonitrile are preferred, as well as unsaturated carboxylic acids and unsaturated carboxylates such as acrylic acid, methacrylic acid, and acrylic and methacrylic acid esters having alkyl esters with 1 to 12 carbon atoms. The shell portion can be formed by graft polymerization with the above-mentioned monomers.

[0063] Furthermore, one or more reactive groups selected from epoxy groups, hydroxy groups, carboxy groups, alkoxy groups, isocyanate groups, acid anhydride groups, and acid chloride groups can be introduced into the graft portion of the impact modifier, which may improve dispersibility and impact resistance compared to the case of using a rubber graft copolymer that does not contain reactive groups.

[0064] The refractive index of the impact modifier used in the present invention is 1.485 or more and 1.495 or less, preferably 1.487 or more and 1.494 or less, and more preferably 1.490 or more and 1.493 or less. When the refractive index of the methyl methacrylate-alkyl acrylate-styrene copolymer is within the above range, the resin composition has excellent transparency and impact resistance.

[0065] The methyl methacrylate-alkyl acrylate-styrene copolymer may be produced by any of bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization, but emulsion polymerization, i.e., emulsion graft polymerization, is preferred. Specifically, latex is added to a reaction vessel equipped with a stirrer, and then monomers, a polymerization initiator, and water are added, and a chain transfer agent and an oxidation-reduction agent are added as necessary, followed by heating and stirring.

[0066] The types of polymerization initiator, chain transfer agent, and redox agent used here are not particularly limited, and known ones can be used. The method of adding each raw material to a reaction vessel is also not particularly limited, and they may be added all at once before the start of polymerization, or may be added in portions. The graft polymerization is carried out in one or more stages, and the monomer composition in each stage may be the same or different. The monomers may be added all at once, continuously, or in a combination of these.

[0067] When the emulsion polymerization method is employed, known polymerization initiators can be used, i.e., thermal decomposition type polymerization initiators such as 2,2'-azobisisobutyronitrile, hydrogen peroxide, potassium persulfate, and ammonium persulfate. In addition, t-butylperoxyisopropyl carbonate, paramenthane hydroperoxide, cumene hydroperoxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, t-hexyl peroxide, and the like can be used. It can also be used as a redox type polymerization initiator in which a peroxide such as an organic peroxide such as silperoxide, or an inorganic peroxide such as hydrogen peroxide, potassium persulfate, or ammonium persulfate is used in combination with a reducing agent such as sodium formaldehyde sulfoxylate or glucose, if necessary, a transition metal salt such as iron (II) sulfate, if necessary, a chelating agent such as disodium ethylenediaminetetraacetate, if necessary, and a phosphorus-based flame retardant such as sodium pyrophosphate, if necessary, and the like.

[0068] When a redox type polymerization initiator system is used, the polymerization can be carried out even at a low temperature where the peroxide does not substantially decompose thermally, so that the polymerization temperature can be set in a wide range, which is preferable. Among them, it is preferable to use an aromatic ring-containing peroxide such as cumene hydroperoxide or dicumyl peroxide as the redox type polymerization initiator. The amount of the polymerization initiator used, and the amount of the reducing agent, transition metal salt, chelating agent, etc. used when a redox type polymerization initiator is used can be within a known range.

[0069] When synthesizing the impact modifier by emulsion polymerization, a conventionally known polymerizable emulsifier can be used as the polymerizable emulsifier, such as an alkali metal salt of a higher fatty acid, such as disproportionated rosin acid, oleic acid, or stearic acid, or an alkali metal salt of a phosphoric acid compound, or an alkali metal salt of a sulfonic acid or a sulfuric acid compound.

[0070] When the impact modifier is obtained by emulsion polymerization, for example, the latex of the impact modifier is mixed with an acid such as hydrochloric acid or a divalent or higher metal salt such as calcium chloride, magnesium chloride, magnesium sulfate, aluminum chloride, calcium acetate, etc., to coagulate the mixture, and then heat-treated, dehydrated, washed, and dried according to a known method to separate the impact modifier from the aqueous medium (also called the coagulation method). Alternatively, a water-soluble organic solvent such as an alcohol such as methanol, ethanol, or propanol, or acetone can be added to the latex to precipitate the impact modifier, and the impact modifier can be separated from the solvent by centrifugation or filtration, and then dried and isolated. Another method is to add an organic solvent having a small water solubility such as methyl ethyl ketone to the latex containing the impact modifier used in the present invention to extract the impact modifier component in the latex into the organic solvent layer, and after separating the organic solvent layer, mix it with water or the like to precipitate the impact modifier component. Alternatively, the latex can be directly powdered by a spray drying method.

[0071] (Epoxy resin) The epoxy resin (D) used in the resin composition of the present invention is not particularly limited as long as it is a compound having an "epoxy group" structure. Epoxy compounds include epoxy group-containing polymers, multifunctional epoxy compounds, etc., which are generally widely known, and any of them can be used. Examples of epoxy compounds include those described in Japanese Patent No. 6146989 and the like.

[0072] The molecular weight of the epoxy resin is preferably 300 to 20000, more preferably 500 to 15000, even more preferably 1000 to 13000, and most preferably 2000 to 12000. Within such ranges, the compatibility with polycarbonate resin is excellent, the transparency when molded into a molded article is excellent, deterioration of color due to decomposition of the epoxy resin itself during molding is further suppressed, and excellent moisture and heat resistance and light resistance can be obtained.

[0073] In this specification, when the epoxy resin is a polymer, the molecular weight of the epoxy resin means the "weight average molecular weight". Here, the weight average molecular weight of the epoxy resin is the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight of the epoxy resin in terms of polystyrene is measured using a measuring device LC-9A / RID-6A manufactured by Shimadzu Corporation, The measurement is performed using Shodex K-800P / K-804L / K-804L manufactured by Showa Denko K.K. as the column and chloroform or the like as the mobile phase at a column temperature of 40° C., and calculation can be performed using a calibration curve of standard polystyrene.

[0074] As the epoxy resin, commercially available products may be used, and examples thereof include epoxy group-containing polymers ("G-0150M" manufactured by NOF Corp., "UG-4010" manufactured by Toa Gosei Corp., and epoxy group-containing acrylic-styrene polymers ("UG-4035" manufactured by Toa Gosei Corp.).

[0075] (Method of producing resin composition) The resin composition of the present invention is preferably prepared by blending polycarbonate resin, methyl methacrylate-methyl acrylate copolymer, methyl methacrylate-alkyl acrylate-styrene copolymer and epoxy resin in a molten state. As a method for blending in a molten state, an extruder is generally used, and the molten resin is kneaded at a temperature of 200 to 320°C, preferably 220 to 300°C, more preferably 230 to 290°C, and pelletized. This provides pellets of a resin composition in which both resins are uniformly blended. The configuration of the extruder, the configuration of the screw, etc. are not particularly limited. If the molten resin temperature in the extruder exceeds 320°C, the resin may become discolored or may undergo thermal decomposition. On the other hand, if the resin temperature is below 200°C, the resin viscosity may be too high and the extruder may be overloaded.

[0076] (weight ratio) The weight ratio of the polycarbonate resin to the methyl methacrylate-methyl acrylate copolymer is preferably in the range of 50:50 to 99:1, more preferably in the range of 52:48 to 95:5, even more preferably in the range of 54:46 to 93:7, particularly preferably in the range of 56:35 to 90:10, and most preferably in the range of 60:40 to 88:12. By keeping the ratio in the above range, a resin composition having superior surface hardness and impact resistance can be obtained.

[0077] The methyl methacrylate-alkyl acrylate-styrene copolymer is mixed in the range of 10 to 30 parts by weight per 100 parts by weight of the total of the polycarbonate resin and the methyl methacrylate-methyl acrylate copolymer. The range is preferably 11 to 28 parts by weight, more preferably 12 to 26 parts by weight, even more preferably 13 to 23 parts by weight, and particularly preferably 14 to 20 parts by weight. By adjusting the range to the above, a resin composition excellent in transparency, surface hardness, and impact resistance can be obtained.

[0078] The epoxy resin is mixed in the range of 1 to 30 parts by weight per 100 parts by weight in total of the polycarbonate resin and the methyl methacrylate-methyl acrylate copolymer. The range is preferably 2 to 25 parts by weight, more preferably 3 to 20 parts by weight, even more preferably 4 to 15 parts by weight, and most preferably 5 to 10 parts by weight. By adjusting the range to the above, a resin composition excellent in transparency, impact resistance, moist heat resistance, and dry heat resistance can be obtained.

[0079] (Additives) The resin composition used in the present invention may contain additives such as a heat stabilizer, a plasticizer, a light stabilizer, a polymerized metal deactivator, a flame retardant, a lubricant, an antistatic agent, a surfactant, an antibacterial agent, an ultraviolet absorber, a release agent, and a colorant, depending on the application and need.

[0080] (Heat stabilizer) The resin composition used in the present invention preferably contains a heat stabilizer in order to suppress the decrease in molecular weight and the deterioration of color during extrusion and molding. Examples of the heat stabilizer include phosphorus-based heat stabilizers, phenol-based heat stabilizers, and sulfur-based heat stabilizers. These may be used alone or in combination of two or more. The above can be used in combination. It is preferable to use a phosphite compound as the phosphorus-based stabilizer. Examples of the phosphite compound include pentaerythritol-type phosphite compounds, phosphite compounds having a cyclic structure due to reaction with dihydric phenols, and phosphite compounds having other structures.

[0081] Specific examples of the pentaerythritol phosphite compound include distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, dicyclohexyl pentaerythritol diphosphite, and the like. Among these, distearyl pentaerythritol diphosphite and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite are preferred.

[0082] Examples of the phosphite compounds having a cyclic structure that react with the above dihydric phenols include 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, phosphite, 2,2'-ethylidenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-methylene-bis-(4,6-di-t-butylphenyl)octylphosphite, 6-tert-butyl-4-[3-[(2,4,8,10)-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]propyl]-2-methylphenol, and the like.

[0083] Examples of phosphite compounds having the above other structures include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tris(diethylphenyl)phosphite, tris(di-isopropylphenyl)phosphite, tris(di-n-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, and tris(2,6-di-tert-butylphenyl)phosphite.

[0084] In addition to the various phosphite compounds, examples of the compounds include phosphate compounds, phosphonite compounds, and phosphonate compounds.

[0085] Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, and the like, and preferably triphenyl phosphate and trimethyl phosphate.

[0086] The phosphonite compound is tetrakis(2,4-di-tert-butylphenyl) -4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis(2,4-di-tert-butylphenyl) )-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, etc. are exemplified, with tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite being preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite being more preferred. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.

[0087] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.

[0088] Among the above phosphorus-based heat stabilizers, trisnonylphenyl phosphite, trimethyl phosphate, tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite are preferably used.

[0089] The phosphorus-based heat stabilizers can be used alone or in combination of two or more kinds. The phosphorus-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight per 100 parts by weight of the resin composition.

[0090] In order to suppress the decrease in molecular weight and deterioration of color during extrusion and molding, the resin composition used in the present invention may also contain a heat stabilizer such as a hindered phenol-based heat stabilizer or a sulfur-based heat stabilizer in combination with a phosphorus-based heat stabilizer.

[0091] The hindered phenol-based heat stabilizer is not particularly limited as long as it has an antioxidant function. Examples of the hindered phenol-based heat stabilizer include n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, tetrakis{methylene-3-(3',5'-di-t-butyl-4-hydroxyphenyl)propionate}methane, distearyl(4-hydroxy-3-methyl-5-t-butylbenzyl)malonate, triethylene glycol-bis{3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate}, 1,6-hexanediol-bis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, pentaerythrityl-tetrakis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 2,2- Thiodiethylene bis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 2,2-thiobis(4-methyl-6-t-butylphenol), 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 2,4-bis{(octyl thio)methyl}-o-cresol, isooctyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,5,7,8-tetramethyl-2(4',8',12'-trimethyltridecyl)chroman-6-ol, 3,3',3",5,5',5"-hexa-t-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, and the like.

[0092] Among these, n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, pentaerythrityl-tetrakis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 3,3',3",5,5',5"-hexa-t-butyl-a,a',a'-(mesitylene-2,4,6-triyl)tri-p-cresol, 2,2-thiodiethylenebis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, and the like are preferred.

[0093] These hindered phenol-based heat stabilizers may be used alone or in combination of two or more.

[0094] The hindered phenol-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight, per 100 parts by weight of the resin composition.

[0095] Examples of sulfur-based heat stabilizers include dilauryl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, laurylstearyl-3,3'-thiodipropionate, pentaerythritol tetrakis (3-laurylthiopropionate), bis [2-methyl-4- (3-laurylthiopropionyloxy) -5-tert-butylphenyl] sulfide, octadecyl disulfide, mercaptobenzimidazole, 2-mercapto-6-methylbenzimidazole, 1,1'-thiobis (2-naphthol), etc. Among the above, pentaerythritol tetrakis (3-laurylthiopropionate) is preferred.

[0096] These sulfur-based heat stabilizers may be used alone or in combination of two or more kinds.

[0097] The sulfur-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight, per 100 parts by weight of the resin composition.

[0098] When a phosphite-based heat stabilizer, a phenol-based heat stabilizer, and a sulfur-based heat stabilizer are used in combination, the total amount of these is preferably 0.001 to 1 part by weight, more preferably 0.01 to 0.3 part by weight, per 100 parts by weight of the resin composition.

[0099] (Release agent) The resin composition used in the present invention may contain a mold release agent in order to further improve releasability from a mold during melt molding, within the scope of the present invention.

[0100] Examples of such release agents include higher fatty acid esters of monohydric or polyhydric alcohols, higher fatty acids, paraffin wax, beeswax, olefin waxes, olefin waxes containing carboxy groups and / or carboxylic anhydride groups, silicone oils, and organopolysiloxanes.

[0101] The higher fatty acid ester is preferably a partial or full ester of a monohydric or polyhydric alcohol having 1 to 20 carbon atoms and a saturated fatty acid having 10 to 30 carbon atoms. Examples of such partial or full esters of a monohydric or polyhydric alcohol and a saturated fatty acid include stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, stearate monosorbitate, stearyl stearate, behenic acid monoglyceride, behenyl behenate, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol tetrapelargonate, propylene glycol monostearate, stearyl stearate, palmityl palmitate, butyl stearate, methyl laurate, isopropyl palmitate, biphenyl biphenate, sorbitan monostearate, 2-ethylhexyl stearate, and the like.

[0102] Of these, stearic acid monoglyceride, stearic acid triglyceride, pentaerythritol tetrastearate, and behenyl behenate are preferably used.

[0103] The higher fatty acid is preferably a saturated fatty acid having a carbon number of 10 to 30. Examples of such fatty acids include myristic acid, lauric acid, palmitic acid, stearic acid, and behenic acid.

[0104] These release agents may be used alone or in combination of two or more. The amount of such release agent to be added is preferably 0.01 to 5 parts by weight based on 100 parts by weight of the resin composition.

[0105] (UV absorber) The resin composition used in the present invention may contain an ultraviolet absorber. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, cyclic iminoester-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers, and among these, benzotriazole-based ultraviolet absorbers are preferred.

[0106] Examples of the benzotriazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-3'-dodecyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenylbenzotriazole, 2-[2'-hydroxy benzotriazole-based ultraviolet absorbers represented by 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2,2'methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], and methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenylpropionate-polyethylene glycol condensate can be mentioned.

[0107] The proportion of such an ultraviolet absorber is preferably 0.01 to 2 parts by weight, more preferably 0.1 to 1 part by weight, and further preferably 0.2 to 0.5 parts by weight, based on 100 parts by weight of the resin composition.

[0108] (Light stabilizer) The resin composition used in the present invention may contain a light stabilizer. The inclusion of a light stabilizer has the advantages of being excellent in terms of weather resistance and making the molded product less susceptible to cracking.

[0109] Examples of the light stabilizer include 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, didecanoic acid bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) ester, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6 -tetramethylpiperidin-2-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, methyl(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)carbonate, bis(2,2,6,6-tetramethyl-4-piperidyl)succinate, bis(2,2,6,6-tetramethyl 4-Octanoyloxy-2,2,6,6-tetramethylpiperidine, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 4-octanoyloxy-2,2,6,6-tetramethylpiperidine, bis(2,2,6,6-tetramethyl-4-piperidyl)diphenylmethane-p,p'-dicarbamate, bis(2,2,6,6-tetramethyl-4-piperidyl)benzene-1,3-disulfonate, bis(2,2,6,6-tetramethyl-4-piperidyl)phenylphosphine Examples of the light stabilizer include hindered amines such as thiophene and the like, and nickel complexes such as nickel bis(octylphenyl sulfide, nickel complex-3,5-di-t-butyl-4-hydroxybenzyl phosphate monoethylate and nickel dibutyl dithiocarbamate. These light stabilizers may be used alone or in combination of two or more. The content of the light stabilizer is preferably 0.001 to 1 part by weight, and more preferably 0.01 to 0.5 parts by weight, based on 100 parts by weight of the resin composition.

[0110] (Bluing agent) The resin composition used in the present invention can be blended with a bluing agent to eliminate the yellow color of the lens due to the polymer or ultraviolet absorbing agent. As the bluing agent, any agent that is used for polycarbonate can be used without any problem. In general, anthraquinone dyes are easily available and are preferred.

[0111] Specific examples of bluing agents include those having the general name Solvent Violet 13 [CA. No (Color Index No) 60725], those having the general name Solvent Violet 31 [CA. No 68210, those having the general name Solvent Violet 33 [CA. No 60725], those having the general name Solvent Blue 94 [CA. No 61500], those having the general name Solvent Violet 36 [CA. No 68210], those having the general name Solvent Blue 97 [Bayer's "Macrolex Violet RR"], and those having the general name Solvent Blue 45 [CA. No 61110].

[0112] These bluing agents may be used alone or in combination of two or more. The bluing agent is preferably used in an amount of 0.1×10 -4 ~2×10 -4 It is mixed in parts by weight.

[0113] (Flame retardant) The resin composition used in the present invention may also contain a flame retardant. Examples of the flame retardant include halogen-based flame retardants such as brominated epoxy resin, brominated polystyrene, brominated polycarbonate, brominated polyacrylate, and chlorinated polyethylene, phosphate-based flame retardants such as monophosphate compounds and phosphate oligomer compounds, organic phosphorus-based flame retardants other than phosphate-based flame retardants such as phosphinate compounds, phosphonate compounds, phosphonitrile oligomer compounds, and phosphonic acid amide compounds, organic metal salt-based flame retardants such as organic sulfonic acid alkali (earth) metal salts, boric acid metal salt-based flame retardants, and stannic acid metal salt-based flame retardants, as well as silicone-based flame retardants, ammonium polyphosphate-based flame retardants, and triazine-based flame retardants. In addition, flame retardant assistants (e.g., sodium antimonate, antimony trioxide, etc.) and drip prevention agents (polytetrafluoroethylene having fibril forming ability, etc.) may be added separately and used in combination with the flame retardant.

[0114] Among the above-mentioned flame retardants, compounds that do not contain chlorine atoms or bromine atoms are more suitable as flame retardants for the molded article of the present invention, which is also characterized by reduced environmental impact, since they reduce factors that are considered undesirable when incinerating or thermally recycling the compounds.

[0115] When a flame retardant is added, the amount is preferably in the range of 0.05 to 50 parts by weight per 100 parts by weight of the resin composition. At 0.05 parts by weight or more, more sufficient flame retardancy is easily achieved, and at 50 parts by weight or less, the strength and heat resistance of the molded product are superior.

[0116] (molded product) The resin composition of the present invention can be molded and processed into various molded products (including sheets and films) by any method such as injection molding, compression molding, injection compression molding, melt film forming, casting, etc., and can be used as molded products such as optical lenses, optical disks, optical films, plastic cell substrates, optical cards, liquid crystal panels, headlamp lenses, light guide plates, diffusion plates, protective films, OPC binders, front panels, housings, trays, water tanks, lighting covers, signboards, plastic windows, etc. In particular, it can be used as members requiring high surface hardness such as front panels, housings, trays, water tanks, lighting covers, signboards, plastic windows, etc.

[0117] (transparency) The haze of a 2 mm thick molded piece of the resin composition of the present invention is preferably 10% or less, more preferably 8% or less, even more preferably 5% or less, and particularly preferably 3% or less. If the haze is within the above range, the range of use as an optical member is not limited, which is preferable.

[0118] (YI) The resin composition of the present invention has a YI of preferably 10 or less, more preferably 9 or less, and particularly preferably 8 or less, of a 2 mm-thick molded piece thereof. When the YI is within the above range, the range of use as an optical member is not limited, which is preferable.

[0119] (Moisture and heat resistance) The resin composition of the present invention preferably has a ΔYI, which indicates a change in hue before and after a moist heat test in which a 2 mm thick molded piece is left stationary for 500 hours under conditions of 80°C x 95% RH, of 10 or less, more preferably 9 or less, and particularly preferably 8 or less. If the ΔYI is within the above range, the range of use as an optical component is not limited, which is preferable.

[0120] (Impact strength) The resin composition of the present invention has a notched Charpy impact strength of 6 kJ / m, measured according to ISO 179. 2 It is preferable that the concentration is 7 kJ / m or more. 2 More preferably, it is 8 kJ / m or more. 2More preferably, the notched Charpy impact strength is 100 kJ / m or more. 2 The following functions are sufficient:

[0121] (Lightfastness) The resin composition of the present invention has a thermal conductivity of 150 mW / cm at 63° C. for a 2 mm thick molded piece. 2 The ΔYI, which indicates the change in color before and after the light resistance test in which the product is left stationary for 200 hours under the above conditions, is 10 or less. It is preferable that YI is equal to or less than 8, and it is particularly preferable that YI is equal to or less than 6. When YI is within the above range, the range of use as an optical member is not limited, which is preferable.

[0122] (Pencil hardness) The resin composition of the present invention preferably has a pencil hardness of F or more, more preferably H or more. In terms of excellent scratch resistance, it is even more preferable that it is 2H or more. The pencil hardness of 4H or less has sufficient function. The pencil hardness can be increased by increasing the weight ratio of the acrylic resin. In the present invention, the pencil hardness refers to a hardness at which no scratch marks are left when the resin of the present invention is rubbed with a pencil having a specific pencil hardness, and it is preferable to use the pencil hardness used in the surface hardness test of the coating film that can be measured according to JIS K-5600 as an index. The pencil hardness becomes softer in the order of 9H, 8H, 7H, 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, and 6B, with the hardest being 9H and the softest being 6B.

[0123] (Surface treatment) Molded articles formed from the resin composition of the present invention can be subjected to various surface treatments. The surface treatment referred to here is a method for forming a new layer on the surface of a resin molded article, such as vapor deposition (physical vapor deposition, chemical vapor deposition, etc.), plating (electroplating, electroless plating, hot-dip plating, etc.), painting, coating, printing, etc., and any commonly used method can be applied. Specific examples of the surface treatment include various surface treatments such as hard coating, water-repellent / oil-repellent coating, ultraviolet absorbing coating, infrared absorbing coating, and metallizing (vapor deposition, etc.). Hard coating is a particularly preferred and necessary surface treatment. EXAMPLES

[0124] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, "parts" means "parts by weight." The resins and evaluation methods used in the examples are as follows.

[0125] 1. Polymer composition ratio (NMR) Each repeating unit was measured by proton NMR using a JNM-AL400 manufactured by JEOL Ltd., and the polymer composition ratio (molar ratio) was calculated.

[0126] 2. Specific viscosity The viscosity was measured using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin dissolved in 100 ml of methylene chloride at 20°C. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls]

[0127] 3. Hayes The haze of a 2 mm thick portion of the three-stage plate obtained by the method described below was measured using a haze meter 300A manufactured by Nippon Denshoku Industries Co., Ltd.

[0128] 4. YI A 2 mm portion of the three-tiered plate obtained by the method described below was cut into a size of 45 mm length x 50 mm width x 2 mm thickness, and the YI was measured using a Nippon Denshoku Kogyo SE-2000 spectrophotometer. The smaller the YI, the less yellow it is.

[0129] 5. Moisture and heat resistance test A 2 mm section of the three-tiered plate obtained by the method described below was cut out to a size of 45 mm length x 50 mm width x 2 mm thickness, and this molded plate was subjected to a test using a small environmental tester S manufactured by Espec Corporation. The test pieces were left to stand for 500 hours in H-241 at 80℃ and 95% RH. The ΔYI was measured before and after the test using a Nippon Denshoku Industries SE-2000 spectrophotometer. The smaller the ΔYI, the smaller the discoloration.

[0130] 6. Notched Charpy impact strength The ISO bending test pieces obtained by the method described below were subjected to measurement of the notched Charpy impact strength in accordance with ISO 179.

[0131] 7.Lightfastness test A 2 mm portion of the three-tiered plate obtained by the method described below was cut out to a size of 45 mm length × 50 mm width × 2 mm thickness, and this molded plate was subjected to a test at 63°C, 150 mW / cm using a metal halide lamp tester (Eye Super UV Tester SUV-W161) manufactured by Iwasaki Electric Co., Ltd. 2 The test pieces were left to stand for 200 hours under the above conditions. The ΔYI was measured before and after the test using a Nippon Denshoku Industries SE-2000 spectrophotometer. The smaller the ΔYI, the smaller the discoloration.

[0132] 8.Pencil hardness Based on JIS K5400, a line was drawn on the surface of the molded product in a thermostatic chamber at an atmospheric temperature of 23°C with a pencil held at a 45 degree angle and a load of 750g applied, and the surface condition was visually evaluated.

[0133] [Polycarbonate resin (A)] A-1: Structural units derived from isosorbide (hereinafter ISS) / structural units derived from 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane (hereinafter SPG) / structural units derived from 1,9-nonanediol (hereinafter ND) = 58 / 38 / 4 (mol%), specific viscosity 0.425 A-2: Structural units derived from ISS / structural units derived from SPG / structural units derived from ND=72 / 21 / 7 (mol%), specific viscosity 0.396 A-3: Structural units derived from ISS / structural units derived from ND=96 / 4 (mol%) decanol-terminated modified resin, specific viscosity 0.366 A-4: Structural units derived from ISS / structural units derived from 1,4-cyclohexanedimethanol (hereinafter referred to as CHDM) = 70 / 30 (mol%), specific viscosity 0.378

[0134] [Methyl methacrylate-methyl acrylate copolymer (B)] Mitsubishi Chemical's ACRYPET VH001 (acrylic resin copolymerized with 95 mol% methyl methacrylate and 5 mol% methyl acrylate)

[0135] [Methyl methacrylate-alkyl acrylate-styrene copolymer (C)] Kaneka Kane Ace M-230 (Refractive index: 1.492)

[0136] [Epoxy resin (D)] D-1: NOF Corporation epoxy group-containing polymer Marproof G-0150M (molecular weight: 10,000, epoxy equivalent: 310) D-2: Epoxy group-containing polymer ARUFON UG-4010 (molecular weight: 2900, epoxy equivalent: 710) manufactured by Toa Gosei Co., Ltd. D-3: Epoxy group-containing acrylic-styrene polymer ARUFON UG-4035 (molecular weight: 11,000, epoxy equivalent: 560) manufactured by Toa Gosei Co., Ltd.

[0137] [Mixture of methyl methacrylate-methyl acrylate copolymer and butadiene-alkyl acrylate-alkyl methacrylate copolymer (E)] Mitsubishi Chemical Acrypet VRL40

[0138] [Example 1] <Production of polycarbonate resin (A)> 294 parts of isosorbide (hereinafter abbreviated as ISS), 400 parts of 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane (hereinafter abbreviated as SPG), 22 parts of 1,9-nonanediol (hereinafter abbreviated as ND), 750 parts of diphenyl carbonate (hereinafter abbreviated as DPC), and 0.8×10 tetramethylammonium hydroxide as a catalyst. -2 parts and barium stearate 0.6 x 10 -4 The part was heated to 200°C in a nitrogen atmosphere and melted. Thereafter, the temperature was raised to 220°C over 30 minutes, and the degree of vacuum was adjusted to 20.0 kPa. Thereafter, the temperature was raised to 240°C over a further 30 minutes, and the degree of vacuum was adjusted to 10 kPa. After maintaining that temperature for 10 minutes, the degree of vacuum was reduced to 133 Pa or less over 1 hour. After the reaction was completed, the mixture was discharged from the bottom of the reaction tank under nitrogen pressure, and while cooling in a water tank, it was cut with a pelletizer to obtain polycarbonate resin (A-1) pellets.

[0139] <Production of Resin Composition> Polycarbonate resin A-1, methyl methacrylate-methyl acrylate copolymer B: Mitsubishi Chemical's Acrylic Pet VH001, methyl methacrylate-alkyl acrylate-styrene copolymer C: Kane Ace M230, Kaneka Corporation, epoxy resin D-1: NOF Corp.'s epoxy-terminated acrylic G-0150M were mixed to a weight ratio of 66.2:10:20:3.8, and then fed to an extruder. Extrusion was performed using a vented twin-screw extruder with a diameter of 30 mmφ [Kobe Steel KTX-30], with a screw rotation speed of 150 rpm, a discharge rate of 20 kg / hr, and a vent vacuum of 3 kPa to obtain pellets. The extrusion temperature was 250 ° C from the feed port to the die. A portion of the obtained pellets was dried in a hot air circulation dryer at 90°C for 6 hours or more, and then molded into evaluation test pieces (ISO bending test pieces (compliant with ISO178, ISO179, ISO75-1 and ISO75-2), three-stage plates (1mmt, 2mmt, 3mmt)) using an injection molding machine at a cylinder temperature of 250°C and a mold temperature of 85°C. The evaluation results are shown in Table 1.

[0140] Example 2 <Production of Resin Composition> Polycarbonate resin (A-2) pellets were obtained using 364 parts of ISS, 221 parts of SPG, 39 parts of ND, and 750 parts of DPC as raw materials, and extruded so that the blend weight ratio of A-2:B:C:D-1 was 66.2:18:12:3.8. Except for this, the same operation and evaluation as in Example 1 were carried out. The results are shown in Table 1.

[0141] Example 3 <Production of Resin Composition> Except for the fact that the blend weight ratio of A-2:B:C:D-1 was 66.2:15:15:3.8, the same operations as in Example 1 were carried out and the same evaluations were carried out. The results are shown in Table 1.

[0142] Example 4 <Production of Resin Composition> Except for the fact that the blend weight ratio of A-2:B:C:D-1 was 65.2:15:15:4.8, the same operations as in Example 1 were carried out and the same evaluations were carried out. The results are shown in Table 1.

[0143] [Example 5] <Production of Resin Composition> Except for the fact that the blend weight ratio of A-2:B:C:D-2:D-3 was 66.2:18:12:2.1:1.7, the same operations and evaluations as in Example 1 were carried out. The results are shown in Table 1.

[0144] [Example 6] <Production of Resin Composition> Except for the fact that the blend weight ratio was PC:B:C:D-2:D-3=63.2:18:12:4.5:2.3, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0145] [Example 7] <Production of Resin Composition> Except for the fact that the blend weight ratio of A-2:B:C:D-2:D-3 was 65.2:15:15:3.2:1.6, the same operations and evaluations as in Example 1 were carried out. The results are shown in Table 1.

[0146] [Example 8] <Production of Resin Composition> Except for the fact that the blend weight ratio of A-2:B:C:D-2:D-3 was 63.2:15:15:4.5:2.3, the same operations and evaluations as in Example 1 were carried out. The results are shown in Table 1.

[0147] Comparative Example 1 <Production of polycarbonate resin> 478 parts of isosorbide (hereinafter abbreviated as ISS), 33.5 parts of 1,9-nonanediol (hereinafter abbreviated as ND), 27.6 parts of decanol, 750 parts of diphenyl carbonate (hereinafter abbreviated as DPC), and 0.0025 parts of barium stearate as a catalyst were heated to 120°C under a nitrogen atmosphere and melted. Then, the mixture was sent to a reaction vessel, and the heat transfer medium temperature of the condenser was adjusted to 40°C, the internal temperature of the resin was adjusted to 170°C, and the degree of vacuum was adjusted to 13.4 kPa over 30 minutes. Then, the degree of vacuum was adjusted to 3.4 kPa over 20 minutes, and the temperature was maintained for 10 minutes. The degree of vacuum was further reduced to 0.9 kPa over 30 minutes, the internal resin temperature was adjusted to 180°C, and this temperature was maintained for 10 minutes. After that, the degree of vacuum was reduced to 0.2 kPa and the resin temperature was increased from 180°C to 225°C over 30 minutes. After the specified viscosity was reached, the resin was discharged from the bottom of the reaction tank under nitrogen pressure, and while being cooled in a water tank, it was cut with a pelletizer to obtain polycarbonate resin (A-3) pellets.

[0148] <Production of Resin Composition> Except for the fact that the blend weight ratio was A-3:B:C:D-1=66.2:18:12:3.8, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0149] Comparative Example 2 <Production of Resin Composition> Polycarbonate resin (A-4) pellets were obtained using 354 parts of ISS, 150 parts of CHDM, and 750 parts of DPC as raw materials, and extruded at a blend weight ratio of A-4:B:C:D-1=66.2:18:12:3.8. Except for this, the same operation and evaluation were carried out as in Example 1. The results are shown in Table 1.

[0150] Comparative Example 3 <Production of Resin Composition> The same procedure as in Example 1 was repeated except that the blend weight ratio was A-2:B:C=70:18:12. The same procedures were carried out and the same evaluations were carried out, and the results are shown in Table 1.

[0151] Comparative Example 4 <Production of Resin Composition> Except for the fact that the Brent weight ratio was A-2:B:C:D-1=66.2:22:8:3.8, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0152] Comparative Example 5 <Production of Resin Composition> Except for the fact that the Brent weight ratio was set to A:E = 70:30, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0153] Comparative Example 6 <Production of Resin Composition> Except for the fact that the Brent weight ratio was A:D-1:E=66.2:3.8:30, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0154] Comparative Example 7 <Production of Resin Composition> Except for the fact that the Brent weight ratios were A:D-2, D-3:E=66.2:2.1:1.7:30, the same procedures and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0155] [Table 1] [Industrial Applicability]

[0156] The resin composition of the present invention is useful for producing optical lenses, optical disks, optical films, plastic cell substrates, and optical covers. It is useful as a component for glass plates, liquid crystal panels, headlamp lenses, light guide plates, diffusion plates, protective films, OPC binders, front panels, housings, trays, aquariums, lighting covers, signs, plastic windows, etc.

Claims

1. The repeating units are composed of carbonate units (a) represented by the following formula (1) and other carbonate units (b), the carbonate units (b) being derived from at least one compound selected from the group consisting of an aliphatic diol compound, an alicyclic diol compound and an aromatic dihydroxy compound, and the polycarbonate resin (A) contains 5 to 85 mol % of carbonate units (a) and 15 to 95 mol % of carbonate units (b) in all repeating units, and contains 40 to 10 mol % of repeating units derived from methyl methacrylate. % methyl methacrylate-methyl acrylate copolymer (B), the weight ratio of the polycarbonate resin (A) to the methyl methacrylate-methyl acrylate copolymer (B) being 50:50 to 99:1, and the refractive index of the methyl methacrylate-alkyl acrylate-styrene copolymer (C) being 1.485 or more and 1.495 or less. 【Chemistry 1】 (In the formula, W represents an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms, R represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent, and m represents an integer of 0 to 10.)

2. The resin composition according to claim 1, wherein the weight average molecular weight of the epoxy resin (D) is 2,000 to 20,000.

3. 3. The resin composition according to claim 1, wherein a haze of a test piece having a thickness of 2 mm is 10% or less.

4. A molded article obtained by molding the resin composition according to any one of claims 1 to 3.

5. A film or sheet formed from the resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Polycarbonate resin composition

    JP1992065461A

  • Polycarbonate resin copolymer and plastic lens

    JP2003160660A

  • Aromatic polycarbonate resin composition and molding thereof

    JP2011219695A

  • Polycarbonate resin composition and molded article using the same

    JP2014201679A

  • Resin composition

    JP2015232091A